Animated Words Clouds to View and Extract Knowledge from Textual Information - Castillo, Felicia De Lucia; Brito, Jessica Oliveira; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
The presentation of information is a very important part of the comprehension of the whole. Therefore, the chosen visualization technique should be compatible with the content to be presented. An easy and fast visualization of the subjects developed by a research group, during certain periods, requires a dynamic visualization technique such as the Animated Word Cloud. With this technique, we were able to use the titles of bibliographic publications of researchers to present, in a clear and straightforward manner, information that is not easily evident just by reading its title. The synchronization of the videos generated from the Animated Word Clouds allows a deeper analysis, a quick and intuitive observation, and the perception of information presented simultaneously.